A Genome-Wide CRISPR/Cas9-Based Screen Identifies Heparan Sulfate Proteoglycans as Ligands of Killer-Cell Immunoglobulin-Like Receptors - Klein, Klara; Hölzemer, Angelique; Wang, Tim; Kim, Tae-Eun; Dugan, Haley L.; Jost, Stephanie; Altfeld, Marcus; Garcia-Beltran, Wilfredo F. (Frontiers in Immunology, 2021)
While human leukocyte antigen (HLA) and HLA-like proteins comprise an overwhelming majority of known ligands for NK-cell receptors, the interactions of NK-cell receptors with non-conventional ligands, particularly carbohydrate antigens, is less well described. We previously found through a bead-based HLA screen that KIR3DS1, a formerly orphan member of the killer-cell immunoglobulin-like receptor (KIR) family, binds to HLA-F. In this study, we assessed the ligand binding profile of KIR3DS1 to cell lines using Fc fusion constructs, and discovered that KIR3DS1-Fc exhibited binding to several human cell lines including ones devoid of HLA. To identify these non-HLA ligands, we developed a magnetic enrichment-based genome-wide CRISPR/Cas9 knock-out screen approach, and identified enzymes involved in the biosynthesis of heparan sulfate as crucial for the binding of KIR3DS1-Fc to K562 cells. This interaction between KIR3DS1 and heparan sulfate was confirmed via surface plasmon resonance, and removal of heparan sulfate from cell surfaces abolished KIR3DS1-Fc binding. Testing of additional KIR-Fc constructs demonstrated that KIR family members containing a D0 domain (KIR3DS1, KIR3DL1, KIR3DL2, KIR2DL4, and KIR2DL5) bound to heparan sulfate, while those without a D0 domain (KIR2DL1, KIR2DL2, KIR2DL3, and KIR2DS4) did not. Overall, this study demonstrates the use of a genome-wide CRISPR/Cas9 knock-out strategy to unbiasedly identify cell surface-expressed ligands of NK-cell receptors. We also uncover a previously unknown binding of various activating and inhibitory KIRs, containing a D0 domain, to heparan sulfate that may play a role in NK-cell receptor signaling and target-cell recognition.